2003
DOI: 10.1352/0047-6765(2003)41<161:eiaaco>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Eyewitness Identification Accuracy: A Comparison of Adults With and Those Without Intellectual Disabilities

Abstract: The effect of variation in the clarity of a witnessed event on the accuracy of eyewitness identification for adults with intellectual disabilities and those without disabilities was examined. Following observation of one of three films (clear, less distinct, or ambiguous) depicting a nonviolent theft, participants were asked to identify the thief from a photo lineup. Across all film conditions, participants with intellectual disabilities made as many correct identifications as did participants without disabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 34 publications
1
12
1
1
Order By: Relevance
“…Further research is urgently needed and should include investigation of performance on sequential lineups which are used in many counties including England and Wales, and some states in America. Taking together the findings from the present study and those of Ericson and Issacs (2003) performance. An initial starting point could be to ensure that the purpose of an identification lineup is made clear and that witnesses are reminded that they do not need to identify anyone if they believe the perpetrator not to be present, for example by providing external prompts to reduce the memory load of retaining the specific instructions.…”
Section: Perpetrator Absent Lineupsmentioning
confidence: 57%
See 1 more Smart Citation
“…Further research is urgently needed and should include investigation of performance on sequential lineups which are used in many counties including England and Wales, and some states in America. Taking together the findings from the present study and those of Ericson and Issacs (2003) performance. An initial starting point could be to ensure that the purpose of an identification lineup is made clear and that witnesses are reminded that they do not need to identify anyone if they believe the perpetrator not to be present, for example by providing external prompts to reduce the memory load of retaining the specific instructions.…”
Section: Perpetrator Absent Lineupsmentioning
confidence: 57%
“…Thus far only two published studies have investigated the performance of witnesses with intellectual disabilities (ID) on identification lineups, and both identified some weaknesses in performance. Ericson and Issacs (2003) found that there were no differences between witnesses with and without ID in their ability to identify the perpetrator from a photo lineup. However, on a lineup containing an innocent suspect those with ID were more likely to make a false identification.…”
Section: The Performance Of Eyewitnesses With Intellectual Disabilitimentioning
confidence: 99%
“…De los datos encontrados se desprende que los sujetos con DI tienden a presentar más problemas al tratar de identificar la fotografía de una persona desconocida vista durante un breve periodo de tiempo, en comparación con sujetos sin DI. Estos resultados confirman los encontrados en otras investigaciones previas (por ejemplo, Ericson y Isaacs, 2003). La pregunta es a qué se debe este déficit y si se puede minimizar su impacto, sobretodo en lo que se refiere a la presencia de falsas alarmas.…”
Section: Discussionunclassified
“…Studies have been conducted on the ability of persons with intellectual disability to identify individuals (Boucher and Lewis, 1992;Ericson and Isaacs, 2003;Manzanero, Recio, Alemany, and Martorell, 2011;Ternes and Yuille, 2008). For example, Ericson and Isaacs (2003), comparing adults with ID to those without ID, found that they were equal in terms of correct identifications, but there were more false alarms among those with ID and they were more likely to guess than those without ID.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ericson and Isaacs (2003), comparing adults with ID to those without ID, found that they were equal in terms of correct identifications, but there were more false alarms among those with ID and they were more likely to guess than those without ID.…”
Section: Introductionmentioning
confidence: 99%